Sunnyside Plaza - Simon, Scott (Little, Brown and Company, 2020)
Wonder meets Three Times Lucky in a story of empowerment as a young woman decides to help solve the mystery of multiple suspicious deaths in her group home. Sally Miyake can't read, but she learns lots of things. Like bricks are made of clay and Vitamin D comes from the sun. Sally is happy working in the kitchen at Sunnyside Plaza, the community center she lives in with other adults with developmental disabilities. For Sally and her friends, Sunnyside is the only home they've ever known. Everything changes the day a resident unexpectedly dies. After a series of tragic events, detectives Esther Rivas and Lon Bridges begin asking questions. Are the incidents accidents? Or is something more disturbing happening? The suspicious deaths spur the residents into taking the investigation into their own hands. But are people willing to listen? Sunnyside Plaza is a human story of empowerment, empathy, hope, and generosity that shines a light on this very special world.